Хвильова оптика у просторі Керра з врахуванням спін-спіральної взаємодії - Pelykh, V. O.; Taistra, Y. V. (Publishing house "Academperiodika", 2019)
We apply an algebraically special solution of the Maxwell equations in the Kerr space-time, which we specify as outgoing in the Chandrasekhar meaning, to obtain the wave vectors of right- and left-polarized waves and prove that the nullity condition of field invariants yield the non-nullity of wave vectors and that the wave vector is not geodesic. We also show how these are related to the analysis of radiation in the Kerr space-time, provided by Starobinskii and Teukolsky.